1991
DOI: 10.3406/socco.1991.986
|View full text |Cite
|
Sign up to set email alerts
|

Les hommes sont des réseaux pensants

Abstract: JEAN-PIERRE DARRE What does the relationships system analysis within groups of farmers, led in terms of network analysis, bring to the knowledge of technical change, or of production and marketing change, in agriculture ? Our observations involve the observation of the material change process. But we mostly seek to connect morphologic types of dialogue networks on the one hand and ways to know and evaluate reality, on the other, in short, the ways the thinking activity is collectively produced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…Following Darré's (1991) approach, we identified discussion networks by focusing on on-going debates among farmers regarding dairy farming, which revolve around the unstable parts of the local norms. This enabled farmers to choose among the many farmers they discussed with on a day-to-day basis, those with whom they specifically discussed dairy farming.…”
Section: Methods and Data Collectionmentioning
confidence: 99%
“…Following Darré's (1991) approach, we identified discussion networks by focusing on on-going debates among farmers regarding dairy farming, which revolve around the unstable parts of the local norms. This enabled farmers to choose among the many farmers they discussed with on a day-to-day basis, those with whom they specifically discussed dairy farming.…”
Section: Methods and Data Collectionmentioning
confidence: 99%
“…Pinpointing our research through Darré's (1991) criteria of interactions, we develop our study around the following elements of interactions between actors (farmers with farmers and farmers with actors across networks) and their sources of knowledge and discourses they produce in relation to their actions and innovativeness. Our unit of analysis thus includes farmers along with their mode of interactions within and outside the community of practice (networks) that links to innovativeness amongst farmers, particularly focusing on innovation that is created within the rural cattle farmer group.…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…The strategy to work with existing dialogue groups, rather than with random groups of farmers, is backed up in the literature on learning and innovation among farmers. Darré (Darré et al ., ; Darré, , ) in his extensive body of work emphasized the central role of dialogue in informal localized groups of farmers in shaping and changing their farming practice. Morgan () in his study of farmers converting to organic farming concluded that regular contact in dialogue groups is crucial to engaging in learning communities.…”
Section: Discussionmentioning
confidence: 99%